2008
DOI: 10.1074/jbc.m707967200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of N-Acetylgalactosamine-4-sulfatase and Galactose-6-sulfatase Expression on Chondroitin Sulfates

Abstract: The sulfatase enzymes, N-acetylgalactosamine-4-sulfatase (arylsulfatase B (ASB)) and galactose-6-sulfatase (GALNS) hydrolyze sulfate groups of CS. Deficiencies of ASB and GALNS are associated with the mucopolysaccharidoses. To determine if expression of ASB and GALNS impacts on glycosaminoglycans (GAGs) and proteoglycans beyond their association with the mucopolysaccharidoses, we modified the expression of ASB and GALNS by overexpression and by silencing with small interference RNA in MCF-7 cells. Content of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 36 publications
(86 citation statements)
references
References 23 publications
3
82
0
1
Order By: Relevance
“…In mammary cells, we found reduced ASB activity, as well as reduced activity of galactose-6-sulfatase (GALNS), steroid sulfatase (STS), and arylsulfatase A (ARSA), in malignant mammary cells compared to normal cells [2]. In MCF-7 cells, modification of expression of ASB was associated with changes in expression of syndecan and decorin, proteoglycans with N-acetylgalactosamine-4-sulfate residues as part of their sulfated glycosaminoglycan (sGAG) component [3]. Reduction of ASB activity was also associated with deficiency of CFTR in cystic fibrosis (CF) cell lines [4], and reduced ASB activity was found in peripheral blood smears from 57 children with CF, compared to 181 control patients [5].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In mammary cells, we found reduced ASB activity, as well as reduced activity of galactose-6-sulfatase (GALNS), steroid sulfatase (STS), and arylsulfatase A (ARSA), in malignant mammary cells compared to normal cells [2]. In MCF-7 cells, modification of expression of ASB was associated with changes in expression of syndecan and decorin, proteoglycans with N-acetylgalactosamine-4-sulfate residues as part of their sulfated glycosaminoglycan (sGAG) component [3]. Reduction of ASB activity was also associated with deficiency of CFTR in cystic fibrosis (CF) cell lines [4], and reduced ASB activity was found in peripheral blood smears from 57 children with CF, compared to 181 control patients [5].…”
Section: Introductionmentioning
confidence: 85%
“…Cross-reactivity of the anti-C4S with CS-E or C6S was excluded by similar tests. Immunoprecipitation was performed as described previously [3].…”
Section: Measurement Of Sulfated Glycosaminoglycans (Sgag)mentioning
confidence: 99%
“…Total sulfated glycosaminoglycans, including C4S, chondroitin 6-sulfate, keratan sulfate, dermatan sulfate, heparan sulfate, and heparin, were measured in NCM460 cells, HT-29 cells, mouse colon following exposure to carrageenan, and colon of ARSB-null mice by sulfated glycosaminoglycan (GAG) assay (Blyscan TM , Biocolor, Ltd., Newtownabbey, Northern Ireland) as described previously (32). C4S was determined following immunoprecipitation of cell or tissue lysates with C4S antibody (4D1, Abnova, Littleton, CO or LY111 Amsbio, LLC, Lake Forest, CA).…”
Section: Methodsmentioning
confidence: 99%
“…ARSB activity was measured in the frozen tissue samples following an established method that used the substrate 4-methyumbilliferyl sulfate (Bhattacharyya and Tobacman 2007;Bhattacharyya et al 2008;Bhattacharyya, Solakyildirim, et al 2010). Then, 20 µl of tissue homogenate and 80 µl of assay buffer (0.05M Na acetate buffer, pH 5.6) were combined with 100 µl of substrate (5 mM 4-MUS in assay buffer) in wells of a microplate.…”
Section: Arsb Activity and Immunostaining In Normal And Malignant Colmentioning
confidence: 99%
“…Recent published work demonstrated that reduced ARSB activity is associated with cystic fibrosis, in which there is accumulation of sulfated polysaccharides, including the sulfated glycosaminoglycans chondroitin sulfate and dermatan sulfate (Bhattacharyya and Tobacman 2007;Bhattacharyya et al 2008;Bhattacharyya, Solakyildirim, et al 2010). Immunohistochemistry and confocal microscopy have shown prominent cell membrane immunostaining for ARSB in human colonic and bronchial epithelial cells and cerebrovascular cells, as well as enzymatic activity in the cell membrane fraction (Bhattacharyya, Solakyildirim, et al 2010;Tobacman 2006, 2009).…”
mentioning
confidence: 99%